(untitled) (Annals of Medical Research, 2024)
Aim: We aim to investigate whether increased perioptic cerebrospinal fluid (CSF) pressure causes changes in the optic sheath diameter and microstructure of the optic nerve in patients with idiopathic intracranial hypertension (IIH). We also aim to investigate the relationship between optic sheath diameter and the optic nerve microstructural changes. Materials and Methods: Our retrospective study is a neuroimaging study of CSF opening pressure-confirmed IIH cases and controls, including 1.5 T magnetic resonance imaging (MRI) and diffusion tensor brain imaging. The optic nerve was evaluated by region of interest (ROI) with diffusion tensor imagine (DTI) and compared with the healthy control. DTI findings were correlated with optic sheath diameters. Results: The ADC and RD values ​​obtained from the left optic nerve were significantly increased compared to the healthy group (p=0.004 and p=0.002, respectively). The FA values ​​obtained from the right and left optic nerves were decreased considerably compared to the healthy group (p=0.035 and p=0.015, respectively). We found that perioptic CSF distance increased in cases with IIH and there was a negative correlation between CSF distance and both optic nerve AD values (Left r=-0.42 and right r=-0.43). Conclusion: Patients with IIH have significant DTI changes in the optic nerve microstructure, which is related to the optical sheath diameter. It may be possible to detect optic nerve damage early with microstructural changes before permanent vision loss develops and to monitor nerve damage with DTI parameters. Early recognition of optic nerve damage due to intracranial high pressure with DTI parameters is important in preventing permanent vision loss.